Developing English Teaching Materials Using Task Generator to Enhance The Seventh Graders’ English Language And 21st Century Skills - Ariatna; Ade Aini Nuran; Watcharaphong Soongpankhao (JEELS (Journal of English Education and Linguistics Studies))
Although extensive research has been carried out on the construction of teaching materials to increase students’ English skills, few studies have investigated how English teaching materials can be developed to sharpen students’ 21st century skills. This paper reports a research and development study on the enhancement of English teaching materials based on Task Generator Model to increase students’ 21st century skills. The study, which was conducted at a private secondary school in Medan, began with a need analysis in which students’ views on learning needs were surveyed. The questionnaire data revealed that the majority of students were in favor of materials which can support their English language and 21st century skills. The task-based materials were then developed and validated by experts (a lecturer and a teacher). The validation data showed that the initial product was deemed practical. There were also positive responses from both the teacher and students about the effectiveness of the task-based materials in supporting students’ English abilities and 21st century skills.Although extensive research has been carried out on the construction of teaching materials to increase students’ English skills, few studies have investigated how English teaching materials can be developed to sharpen students’ 21st century skills. This paper reports a research and development study on the enhancement of English teaching materials based on Task Generator Model to increase students’ 21st century skills. The study, which was conducted at a private secondary school in Medan, began with a need analysis in which students’ views on learning needs were surveyed. The questionnaire data revealed that the majority of students were in favor of materials which can support their English language and 21st century skills. The task-based materials were then developed and validated by experts (a lecturer and a teacher). The validation data showed that the initial product was deemed practical. There were also positive responses from both the teacher and students about the effectiveness of the task-based materials in supporting students’ English abilities and 21st century skills.